The effect of stereotype threat on academic success of female students - AVCI, SÜLEYMAN (My University, 2023)
Stereotype threat occurs when educational institutions remind us of the stereotype that men are more successful in mathematics and that women\"s mathematics achievement is negatively affected. In this study, the effect of stereotype threat on the academic achievement of high school students was examined. In the designed experimental study, there are two experimental groups (threat 1 and 2) and a control group. The effects of two different stereotype threats were compared in the experimental groups. After the explanations to reveal stereotype threat in the experimental groups, a mathematics test was used and the \"State Anxiety and Stereotype Awareness Scale\" was administered at the end of the test. In this study conducted in the 10th grade of high school, data was also obtained from male students. According to the data, while there was no significant difference in terms of academic success between the study groups consisting of female students, it was seen that the academic success of the threat 1 group was higher among males. In terms of academic achievement, threat 1 group shows the greatest inequality between genders. It was observed that the state anxiety levels of female students in the experimental groups increased. According to the findings, in addition to a positive and low-level significant relationship between anxiety and academic success in female students, there is also a mediating relationship between anxiety and stereotype threat and academic success. There is no difference between male student groups. Awareness of stereotypes was low in both genders, and it was concluded that boys\" awareness was higher than girls.
Keywords: Sosyal ve Beşeri Bilimler; Eğitim; Temel Bilimler; Social Sciences and Humanities; Education; Natural Sciences; Temel Bilimler (SCI); Sosyal Bilimler (SOC); Doğa Bilimleri Genel; Sosyal Bilimler Genel; ÇOK DİSİPLİNLİ BİLİMLER; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Natural Sciences (SCI); Social Sciences (SOC); NATURAL SCIENCES, GENERAL; SOCIAL SCIENCES, GENERAL; MULTIDISCIPLINARY SCIENCES; EDUCATION & EDUCATIONAL RESEARCH; Multidisipliner; Sosyal Bilimler ve Beşeri Bilimler; Multidisciplinary; Social Sciences & Humanities